Corporate social responsibility and parental monitoring in the management of violent video game effects on juveniles: a study based on age and education in Chennai - Reshma Soman N; Rithika Shree K, (Journal of Contemporary Research in Management (JCRM), 2024)
Games involving shooting and killing which contain gore scenes raised concerns about the impact it has on Juvenile Behaviour. In the view of companies, the prevailing issue is not only the responsibility of the parents, but also the responsibility of companies such as gaming and media, as they play a major role in it. Since gaming industries also have a responsibility to prevent the juveniles from getting affected by industry practices as well as power to place restrictions on games, it can minimise the impact that these games have on juveniles. The main objective of this research is to examine the impact of CSR on violent video games and also compared this with age groups. The researcher has followed the descriptive research method using a convenient sampling method. The sample size of the study is 200. The findings of the study is that most people think that to reduce the negative effects of these games companies should implement stricter age restrictions like this game is only suitable for certain age groups such as, the impact of violent video games that have been observed from this study is that children become more aggressive compared to before because of these games their aggression has been increased which is totally different from their usual character. In conclusion, although violent video games heavily impact children's behaviour it can be prevented by implementing CSR in gaming companies, and the role of parents also play a significant role in it. By balancing both the responsibilities of Companies and Parents, these measures can significantly reduce the negative effects these games have on juveniles.